A battle tank simulator for eye and hand coordination tasks under horizontal whole-body vibration. Issue 1 (March 2018) - Campos, Luiz CA; Menegaldo, Luciano L
This paper describes the development of a simulator to reproduce gunner's target tracking tasks in a main battle tank, under whole-body vibration conditions. For specifying the vibration and tracking conditions, three-degree-of-freedom acceleration was measured in a tracked armored vehicle, equipped with a 105 mm cannon, running in a battlefield test track. The electrohydraulic dynamics of the turret systems was experimentally identified as black-box autoregressive functions. A pneumatic actuation system and a real-time control software were designed to reproduce horizontal, single-axis periodic motion with the dominant frequency observed in field measurements. The control software displays the target and sight points and acquires the turret pointing command from an adapted gunner's handle joystick. The root mean square error between target and simulated turret position allows assessing gunner's target acquisition and tracking performance under periodic vibration.